Local Restorative Models in the Indonesian Legal System: Exploring the Values of Larwul Ngabal as Living Law in the Resolution of Communal Disputes - Agustinus Jonas Sahetapy (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
Larwul Ngabal is a customary legal system of the Kei community that has functioned as a restorative mechanism for resolving communal disputes. As a living law, Larwul Ngabal reflects the values of justice, harmony, and social balance that remain relevant in the context of Indonesian law. This journal explores the role of Larwul Ngabal in resolving communal conflicts and its potential for integration into the national legal system as a model of locally-based restorative justice.